Strength agent application in mechanical pulps for packaging application - Khairool Azizul, Mohammad (2013)
Paper sheets made from different ratio of recycled fibre (RCF) and TMP fibre were examined. Poly (amideamine) epichorohydrin (PAE) resins with different concentration were added to pulp mixture in order to see the effects on the physical properties of the paper. Handsheets with 60g/m 2 basis weight were evaluated for its wet strength, dry strength, compression strength, zero span tensile strength and bending stiffness. The study has found that handsheet from a high fraction of recycled fibre produced a higher apparent density of the sheet. The recycled fibre sheet also showed better strength properties due to the better bonding between the fibres. The wet pressing seemed to have no significant improvement in the strength of the sheets. It was also proved that PAE resin significantly increased strength for handsheets made from all type of pulp. The optimum addition level was 5mg/g.The study was consistent with the TMP fibres being thicker and less flexible which therefore produced lower density sheet with higher bending resistance.